A magma ocean origin to divergent redox evolutions of rocky planetary bodies and early atmospheres - Jie Deng (Nature Portfolio, 2020)
Applying first-principles molecular dynamic simulations and thermodynamic modelling, the authors suggest a vertical oxygen fugacity gradient in magma oceans of Earth, Mars, and the Moon. Consequently, the study proposes larger planets like Earth to have stronger oxidized upper mantles than smaller bodies such as Mars or the Moon.